Шукшинские психи и шизи (в аспекте психопатической классификации Антония Кемпинского) - Shubin, Roman (Acta Polono-Ruthenica, 2018)
In this article the author considers images of protagonists and the narrator in aspect of psychopathic type of epileptoides, described by Antony Kempinsky. This psychotype in article is beyond especially psychiatric classification and becomes the cultural frame describing aggressive and despotic cultural system with repressions inside and expansion outside, what was socialist system of a period of cold war. Shukshin characters bear on themselves burden of this system: dreaming to become heroes of the country, they focus in themselves negative lines: despotism, hate, anger, rage, rejection. Conflicts between heroes in stories tell about fight of the person against the system which is not leaving freedoms and spirituality. Shukshin artist’s eye snatches out from crowd thin and thick, small and large, weak and strong for heroes and their enemies, but this choice is predetermined by the single psychopathic situation which has been taken out from soul of the writer.